Study Of Parametric Influence In Machining Inconel With WEDM - Dr Ch.V.S.Parameswararao , Dr K.Ravidra, P.SrinivasaRao (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper presents an experimental investigation of machining accuracy on wire cut electrical discharge machining of Inconel75 material of thickness 5mm to 90mm in different sizes. An extensive research has been carried out with an aim to select an appropriatemachining current, cutting speed and spark gap that can be achieved during the machining at the optimum cutting condition, for cuttingInconel75 work piece of any thickness. Mathematical correlations are developed to determine the machining current, cutting speed andspark gap. Statistical analysis is performed to prove its validity. Finally the correlation are useful for evaluating the machine settings for therequired finish, cutting speed, machining time and tool offset for different machining situations arising out of customer requirements.